Developing a health economic model for Asians with type 2 diabetes based on the Japan Diabetes Complications Study and the Japanese Elderly Diabetes Intervention Trial. Issue 1 (5th August 2021) - Tanaka, Shiro; Langer, Jakob; Morton, Tim; Hoskins, Nicki; Wilkinson, Lars; Tanaka-Mizuno, Sachiko; Kawasaki, Ryo; Moriya, Tatsumi; Horikawa, Chika; Aida, Rei; Araki, Atsushi; Fujihara, Kazuya; et al.
Abstract : Introduction: Cost-effectiveness analyses are becoming increasingly important in Japan following the introduction of a health technology assessment scheme. The study objective was to develop an economic model to evaluate the cost-effectiveness of two interventions for type 2 diabetes in a Japanese population. Research design and methods: The Japan Diabetes Complications Study/Japanese Elderly Diabetes Intervention Trial risk engine (JJRE) Cost-Effectiveness Model (JJCEM) was developed, incorporating validated risk equations in Japanese patients with type 2 diabetes from the JJRE. Weibull regression models were developed for progression of the model outcomes, and a targeted literature review was performed to inform default values for utilities and costs. To illustrate outcomes, two simulated analyses were performed in younger (aged 40 years) and older (aged 80 years) Japanese populations, comparing a hypothetical treatment with placebo. Results: The model considers a population based on user-defined values for 11 baseline characteristic parameters and simulates rates of diabetic complications over a defined time horizon. Costs, quality-adjusted life years, and an incremental cost-effectiveness ratio are estimated. The model provides disaggregated results for two competing interventions, allowing visualization of the key drivers of cost and utility. A scatterplot of simulations and cost-effectiveness acceptability curve are generated for each analysis. Conclusions: This is the first cost-effectiveness model for East Asian patients with type 2 diabetes, developed using Japan-specific risk equations. This population constitutes the largest share of the global population with diabetes, making this model highly relevant. The model can be used to evaluate the cost-effectiveness of anti-diabetic interventions in patients with type 2 diabetes in Japan and other East Asian populations.